2010
DOI: 10.1093/jxb/erq347
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for phenotypic plasticity in the Antarctic extremophile Chlamydomonas raudensis Ettl. UWO 241

Abstract: Life in extreme environments poses unique challenges to photosynthetic organisms. The ability for an extremophilic green alga and its genetic and mesophilic equivalent to acclimate to changes in their environment was examined to determine the extent of their phenotypic plasticities. The Antarctic extremophile Chlamydomonas raudensis Ettl. UWO 241 (UWO) was isolated from an ice-covered lake in Antarctica, whereas its mesophilic counterpart C. raudensis Ettl. SAG 49.72 (SAG) was isolated from a meadow pool in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Snow algae from the genera Chloromonas and Chlamydomonas were considered to be obligate cryophiles with optimal growth below 10 °C (Hoham, ). Low temperature growth optima were reported, for example for Chloromonas pichinchae (1 °C; Hoham, ), Chloromonas chenangoensis , Chloromonas tughillensis (2.5–5 °C; Hoham et al ., ), C. raudensis (8 °C; Pocock et al ., ) and Chlamydomonas sp. (5 °C; Eddie et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Snow algae from the genera Chloromonas and Chlamydomonas were considered to be obligate cryophiles with optimal growth below 10 °C (Hoham, ). Low temperature growth optima were reported, for example for Chloromonas pichinchae (1 °C; Hoham, ), Chloromonas chenangoensis , Chloromonas tughillensis (2.5–5 °C; Hoham et al ., ), C. raudensis (8 °C; Pocock et al ., ) and Chlamydomonas sp. (5 °C; Eddie et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…To characterize the IBPs of a second chlamydomonad alga, we selected C. raudensis UWO241, a species that was isolated from a permanently ice-covered Antarctic lake [5], [6] and that has been the subject of many studies on the adaptation to extreme conditions, including low light [7], low temperature [8] and high salinity [9]. We obtained the IBP sequences of C. raudensis UWO241 by sequencing the transcriptome, confirmed that they encode IBPs, and compared the ice-binding activities of C. raudensis UWO241 and a mesophilic sister species.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their diversity, snow algae share their main property: Their optimum growth temperatures are generally around 0 o C (Teoh et al 2004). To adapt to this harsh environment, they developed a number of adaptive features, which include biosynthesis of pigments (Fong et al 2001), polyols (Arnold et al 2003, Leya et al 2009), sugars (Arnold et al 2003, lipids, and spore formation (Pocock et al 2011, Zang et al 2003. The spores, which withstand subzero temperatures in winter, usually have large amounts of lipid reserves, polyols and sugars (Rezanka et al 2008).…”
mentioning
confidence: 99%